CNS Aquaporin‐4‐specific B cells connect with multiple B‐cell compartments in neuromyelitis optica spectrum disorder. Issue 6 (9th May 2017) - Kowarik, Markus C.; Astling, David; Gasperi, Christiane; Wemlinger, Scott; Schumann, Hannah; Dzieciatkowska, Monika; Ritchie, Alanna M.; Hemmer, Bernhard; Owens, Gregory P.; Bennett, Jeffrey L.
Abstract: Objectives: Neuromyelitis optica spectrum disorder (NMOSD) is a severe inflammatory disorder of the central nervous system (CNS) targeted against aquaporin‐4 (AQP4). The origin and trafficking of AQP4‐specific B cells in NMOSD remains unknown. Methods: Peripheral ( n = 7) and splenic B cells ( n = 1) recovered from seven NMOSD patients were sorted into plasmablasts, naïve, memory, and CD27‐IgD‐ double negative (DN) B cells, and variable heavy chain (VH) transcriptome sequences were generated by deep sequencing. Peripheral blood (PB) VH repertoires were compared to the same patient's single‐cell cerebrospinal fluid (CSF) plasmablast (PB) VH transcriptome, CSF immunoglobulin (Ig) proteome, and serum Ig proteome. Recombinant antibodies were generated from paired CSF heavy‐ and light chains and tested for AQP4 reactivity. Results: Approximately 9% of the CSF VH sequences aligned with PB memory B cells, DN B cells, and plasmablast VH sequences. AQP4‐specific VH sequences were observed in each peripheral B‐cell compartment. Lineage analysis of clonally related VH sequences indicates that CSF AQP4‐specific B cells are closely related to an expanded population of DN B cells that may undergo antigen‐specific B‐cell maturation within the CNS. CSF and serum Ig proteomes overlapped with the VH sequences from each B‐cell compartment; the majority of matches occurring between the PB VH sequences and serum Ig proteome. Interpretation: During an acute NMOSD relapse, a dynamic exchange of B cells occurs between the periphery and CNS with AQP4‐specific CSF B cells emerging from postgerminal center memory B cells and plasmablasts. Expansion of the PB DN B‐cell compartment may be a potential biomarker of NMOSD activity.